Notonuphar antarctica, an extinct water lily (Nymphaeales) from the Eocene of Antarctica - Friis, Else M. (2017)
A new genus and species, Notonuphar antarctica, is described from the Eocene of Seymour (Marambio) Island, the Antarctic Peninsula and assigned to the Nymphaeales based on well-preserved seeds. This is the first record of a water lily from Antarctica and the first record of a Gondwanan plant with close link to the genus Nuphar (Nymphaeaceae), which is restricted today to the Northern Hemisphere. Critical features for systematic placement of Notonuphar are the presence of a germination cap with closely spaced hilar scar and micropyle, anatropous, bitegmic and exotestal seed organization, exotesta composed of one cell layer of high sclerenchymatic palisade-shape cells, mesotesta of smaller, low parenchymatic cells, a few cell layers deep, and a thin tegmen. The seeds of Notonuphar are particularly similar to seeds of extant and fossil Nuphar in the straight, unfolded anticlinal wall of the exotestal cells and the presence of a narrow zone of exotestal tissue between hilum and micropyle. Other seed features including the very tall exotestal cells and strongly thickened cell walls of exotesta also link Notonuphar to Brasenia and related fossil taxa (Cabombaceae). This character mosaic observed in Notonuphar corroborates the transitional position of Nuphar between Cabombaceae and Nymphaeaceae. Notonuphar is the only member of Nymphaeales recorded from Antarctica and so far the only fossil seeds of Nymphaeales known from the Southern Hemisphere. The discovery of this extinct Gondwanan taxon with features suggesting close relationship with extant Northern Hemisphere genus Nuphar is a further evidence for the relictual nature of the extant group.